The Role of Leaf Fodder in Animal Husbandry of the United Provinces - Chaturvedi, M. D. (Indian Forester, 1944)
During the cold weather when grasses become inedible, leaf fodder supplements the food resources of 5 out of 39 million domestic animals in the United Provinces. Introduction of leaf fodder species in the plantations both in the reserved and private forests, afforestation of wastelands and effective control of lopping will go a long way towards the development of this important source of food supply of the tivestock in these provinces.